2008
DOI: 10.1074/jbc.m709549200
|View full text |Cite
|
Sign up to set email alerts
|

CpG DNA Prevents Liver Injury and Shock-mediated Death by Modulating Expression of Interleukin-1 Receptor-associated Kinases

Abstract: Tumor necrosis factor-␣ (TNF-␣) produced by macrophages in response toThe innate immune response is initiated by recognition of evolutionarily conserved molecular motifs (pathogen-associated molecular patterns) found in a variety of microorganisms by pattern recognition receptors present in the host innate immune cells (1, 2). Among the pattern recognition receptors, Toll-like receptors (TLRs) 4 are the most extensively investigated. TLRs are a group of structurally related proteins that contain amino-termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 53 publications
1
32
0
Order By: Relevance
“…Also, accumulating evidence suggests that NF-κB can regulate the network of inflammatory cytokines in hepatic injury induced by Con A [26,27]. Our data showed that CpG pretreatment prevented NF-κB DNA-binding activity, IκBα phosphorylation and the expression of proinflammatory cytokines including TNF-α and IFN-γ, which correlate with those showing CpG ODN-mediated protection from DNA/DGalN-induced liver injury and polymicrobial sepsis induced by the rat cecal ligation and puncture (CLP) model [10,28]. The attenuated activation of NF-κB in CpG ODN pretreated mice livers may contribute to the protective effects of CpG ODN on Con Ainduced hepatitis.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Also, accumulating evidence suggests that NF-κB can regulate the network of inflammatory cytokines in hepatic injury induced by Con A [26,27]. Our data showed that CpG pretreatment prevented NF-κB DNA-binding activity, IκBα phosphorylation and the expression of proinflammatory cytokines including TNF-α and IFN-γ, which correlate with those showing CpG ODN-mediated protection from DNA/DGalN-induced liver injury and polymicrobial sepsis induced by the rat cecal ligation and puncture (CLP) model [10,28]. The attenuated activation of NF-κB in CpG ODN pretreated mice livers may contribute to the protective effects of CpG ODN on Con Ainduced hepatitis.…”
Section: Discussionsupporting
confidence: 76%
“…TNF-α was primarily released by activated T cells and Kuppfer cells in the livers of Con A treated mice. A previous study demonstrated that macrophages (both Kuppfer cells and RAW264.7) pretreated with CpG ODN became hyporesponsive to the following CpG ODN stimulation through modulating the expression of interleukin-1 receptor-associated kinases [10,24]. Our data suggest that CpG ODN pretreatment may function in vivo by inducing macrophage's hyporesponsiveness to Con A.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Transfection-Retroviral vectors expressing Myc-tagged Syk and Zap-70 as well as FLAG-tagged FcR␥ and TCR-were developed as previously described (14). Briefly, the coding region of each was amplified by PCR using murine spleen cDNA as a template and then inserted into a pIRES-hrGFPII (Stratagene, La Jolla, CA) vector.…”
Section: Methodsmentioning
confidence: 99%